Obesity and renal disease: Benefits of bariatric surgery - Ardiles, Leopoldo G. (Frontiers in Medicine, 2023)
The prevalence of obesity, a preventable and reversible condition with a high impact on health, continues to rise, especially after the COVID-19 pandemic. Severe overweight is well recognized as a risk factor for diabetes and hypertension, among other conditions, that may increase cardiovascular risk. Obesity has grown simultaneously with a rise in the prevalence of chronic kidney disease, and a pathophysiological link has been established, which explains its role in generating the conditions to facilitate the emergence and maximize the impact of the risk factors of chronic kidney disease and its progression to more advanced stages. Knowing the mechanisms involved and having different tools to reverse the overweight and its consequences, bariatric surgery has arisen as a useful and efficient method, complementary or alternative to others, such as lifestyle changes and/or pharmacotherapy. In a detailed review, the mechanisms involved in the renal consequences of obesity, the impact on risk factors, and the potential benefit of bariatric surgery at different stages of the disease and its progression are exposed and analyzed. Although the observational evidence supports the value of bariatric surgery as a renoprotective measure in individuals with obesity, diabetic or not, randomized studies are expected to establish evidence-based recommendations that demonstrate its positive risk–benefit balance as a complementary or alternative therapeutic tool.